RETAINED GAUZE PIECE RESULTING IN RIGHT RENAL COMPLEX CYST DIAGNOSED AFTER 4 YEARS OF PYELOLITHOTOMY - Arshad, Ayra; Zehra, Nayyab; Malik, Ahmed Hassaan (Journal of Ayub Medical College Abbottabad, 2015)
Renal cysts are the most common space occupying lesions of kidneys. These may be simple or complex. Complex renal cysts are suspicious for malignancy. Computed tomography is the gold standard in diagnosis of complex renal cysts. Negligence resulting in retained surgical foreign bodies does occur in our setup and world over. We present a unique case of retained gauze piece presenting as complex renal cyst, diagnosed four years after pyelolithotomy. A 50 year old male presented with history of on and off right lumbar pain for the last one year, along with low grade intermittent fever and weight loss. Past history revealed that he was operated for renal stones four years ago. Radio imaging including ultrasonography and CT scan revealed complex renal cyst. Patient was explored and found to have thick walled cyst with old gauze in it. Keywords: Retained gauze, pyelolithotomy complication, complex renal cyst